Estimativas de parâmetros genéticos e fenotípicos para peso corporal e características de carcaça em codorna de corte - Paiva, Emilia de (2007)
The purpose of this work were to estirnate genetic and phenotypic parameters for body weight at birth, 7, 14, 21, 28 and 35 days of age and to calculate the efficiency in producing genetic improvement in the body weight at 35 days due to selection based on body weight at 21 or 28 days as well as to estirnate genetic and phenotypic parameters for body weight at 28 and 35 days of age and carcass traits for meat quails. The data were analyzed by Bayesian procedures, using Gibbs sampler. The heritability estimative for body weights at birth, 7, 14, 21, 28 and 35 days of age were respectively 0.25, 0.03, 0.13, 0.15, 0.18, and 0.24, indicating that the selection should be based on the predicted of genetic value using the animal model and all available information. The genetic correlations between weight at birth and weights at 7, 14, 21, 28 and 35 days of age were 0.02, 0.19, 0.16, 0.12 and 0.11 respectively; between weight at 7 and weights at 14, 21, 28 and 35 days of age were 0.3 1, 0.27, 0.23 and 0.17 respectively; between weight at 14 and weights at 21, 28 and 35 days of age were 0.79, 0.66 and 0.54 respectively; between weight at 21 and weights at 28 and 35 days of age were 0.84 and 0.76 respectively, and between weights at 28 and 35 days of age was 0.87. The selection efficiency based on weights at 21 and 28 days of age to obtain genetic improvement in weight at 35 days were 69% and 75%. The genetic correlations obtained between the weights in the different ages indicate that genetic improvement can be successfully obtained using the weight at 28 days as a selection criterion. The heritability estimative, for body weight at 28 days of age, chest width, carcass weight, chest weight and thigh and on-thigh weight were respectively, 0.12, 0.92, 0.72, 0.65 and 0.18. The heritability estimates, for weight at 35 days of age and the same carcass traits were respectively, 0.16, 0.90, 0.63, 0.60 and 0.17. The estimates of genetic correlations of weights at 28 and 35 days of age for carcass traits were from medium to high and practically the same, indicating that the selection based on the weight at 28 days of age would improve the carcass traits like those obtained if the selection was based on the weight at 35 days of age. The chest width showed a low genetic correlation with carcass and chest weights, and a medium correlation with the thigh and on-thigh weight. The carcass weight showed a high genetic correlations with chest weight and thigh and on-thigh weight, but the genetic correlation between chest and thigh and on-thigh weights was very low. The results indicate that the use of weight at 28 or 35 days of age as selection criterion produces similar genetic improvement in the carcass weight, chest, thigh and on-thigh.